2017
DOI: 10.5696/2156-9614-7.15.40
|View full text |Cite
|
Sign up to set email alerts
|

A Market Basket Survey of Horticultural Fruits for Arsenic and Trace Metal Contamination in Southeast Nigeria and Potential Health Risk Implications

Abstract: Background.Elevated arsenic and trace metal contamination of the terrestrial food chain represents one of the most significant environmental risk exposures for human populations in developing countries. Metalloid and metal contamination in horticultural crop produce such as fruit is a public health concern in Nigeria. Local fruits are cheap sources of vitamins and minerals for the resident population and pose an important dietary threat of metal(loid) toxicity through consumption.Objectives.Market basket inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The approach, however, is unsystematically planned to enable the sustainability of other dependent urban functions and contain spillovers. The strategic implication of this uncoordinated development is that air quality will continue to deteriorate until Anambra State realigns land-use zoning priorities and balances economic development and the environment with appropriate sustainable regulatory instruments [6,65,66]. Our results are not an isolated incident, as similar outcomes have been reported elsewhere in Southeastern Nigeria.…”
Section: Air Quality Indexsupporting
confidence: 68%
“…The approach, however, is unsystematically planned to enable the sustainability of other dependent urban functions and contain spillovers. The strategic implication of this uncoordinated development is that air quality will continue to deteriorate until Anambra State realigns land-use zoning priorities and balances economic development and the environment with appropriate sustainable regulatory instruments [6,65,66]. Our results are not an isolated incident, as similar outcomes have been reported elsewhere in Southeastern Nigeria.…”
Section: Air Quality Indexsupporting
confidence: 68%
“…On the other hand, the TTHQ was not >1, and it was concluded that all the studied fruits and vegetable were safe to consume. However, a previous study reported the heavy metal status and presence of arsenic in a rural area in Bangladesh [25], and the levels of trace metals have also been mentioned in the vegetables growing near a mining area in Andhra Pradesh (India, southeast Nigeria) [26][27][28]. Figure 6 depicts the health risk index of iron, manganese, and zinc with HI < 1.…”
Section: Resultsmentioning
confidence: 98%
“…However, the maximum concentration exceeded FAO/WHO recommended limit for public health of consumers. Persistent exposure to high levels of inorganic As has severe health risk implications, including anaemia, diarrhoea, liver damage, hypertension and skin disease [17,32]. Lead (Pb) is a known hazardous metal to human health [1].…”
Section: Resultsmentioning
confidence: 99%
“…Each analytical batch of ten runs was accompanied by an acid blank and three certified reference materials (CRM). Mean recoveries were in an acceptable range (90 -99.5%) compared to the CRM theoretical or certified values for the metals [17]. Results were expressed in mg kg −1 dry weight with instrumental detection limit of 0.001 mg kg −1 dry weight and compared with FAO/WHO Codex Alimentarius (or Food Code).…”
Section: Sampling Preparation and Analysismentioning
confidence: 93%
See 1 more Smart Citation